A controlled thiol-initiated surface polymerization strategy for the preparation of hydrophilic polymer stationary phases. Issue 79 (24th August 2015) - Yu, Dongping; Shen, Aijin; Guo, Zhimou; Yan, Yukun; Yan, Jingyu; Jin, Gaowa; Liang, Xinmiao
Abstract : A controlled thiol-initiated surface polymerization strategy has been successfully developed and employed to prepare hydrophilic polymer stationary phases, which exhibited excellent chromatographic performance and protein non-fouling properties. Abstract : A controlled thiol-initiated surface polymerization strategy has been successfully developed and employed to prepare hydrophilic polymer stationary phases, which exhibited excellent chromatographic performance and protein non-fouling properties.